Intermediate Financial Accounting Volume 2 - Arnold, Glenn; Kyle, Suzanne; Open Textbook Library (Open Textbook Library, 2017)
This new text by G. Arnold and S. Kyle, developed in collaboration by Athabasca University and Lyryx, is intended for the second of two in Intermediate Financial Accounting courses. It presumes that students have already completed the Introductory Financial Accounting, and the first Intermediate Financing Accounting course. The text reflects both current International Financial Reporting Standards (IFRS) and ASPE. This text covers all topics essential to a second level Intermediate Accounting course: current, long-term and complex liabilities, income taxes, pensions, leases, shareholders' equity, earnings per share, statement of cash flows including the direct approach, effects of changes and errors, and disclosures and analysis. Topics that are covered in Advanced Financial Accounting courses, such as consolidations and foreign exchange, are not included here.
12 Current Liabilities -- 13 Long-Term Financial Liabilities -- 14 Complex Financial Instruments -- 15 Income Taxes -- 16 Pensions and Other Employment Benefits -- 17 Leases -- 18 Shareholders' Equity -- 19 Earnings per Share -- 20 Statement of Cash Flows -- 21 Changes and Errors -- 22 Putting It All Together: Disclosures and Analysis Overview -- Solutions To Exercises
In English.
Description based on print resource
Keywords: Business -- Textbooks; Accounting -- Textbooks; Finance -- Textbooks